A study on the physicochemical properties of defatted New Zealand green-lipped mussel protein concentrates (MPC) dispersions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology, Massey University, Auckland, New Zealand. EMBARGOED until 28th July 2026 - Lin, Jingying (Massey University, 2024)
This thesis investigated changes of physicochemical properties of mussel protein concentrates (MPC) dispersions at different pH affected by ultrasound treatment and the viscoelastic properties of heat-induced MPC gels with varying concentrations of different starches. The first study evaluated the effect of pH (3,5,7,9) and ultrasound treatment (15 min) on the physicochemical and functional properties of desalted MPC, including particle size, solubility, zeta potential, emulsification, and gelation. Compared with control groups, it was found that the particle size of all samples at all pH decreased greatly after ultrasound treatment, as reflected in a 7~17 times reduction in D [3,2] and a 3~8 times reduction in D [4,3]. Ultrasound treatment also improved absolute values of zeta potential and made MPC dispersions more stable. In addition, ultrasound treatment increased the solubility of MPC dispersions at all pH values. The most significant increase in solubility was observed for samples at pH 3, from ~1.2% to ~57.4%; followed by pH 7 and pH 9 samples, from ~1% to ~20.8% and ~2% to ~18.7%, respectively; pH 5 showed the smallest change, from ~0.5% to ~0.8%, which was because it closed to the isoelectric point of MPC (pI~4.55). SDS-PAGE results showed that MPC composed of actin (43-46 kDa) and paramyosin (98–107 kDa), ultrasound treatment and pH changes did not result in significant changes in the mussel protein bands. All untreated and sonicated MPC samples were observed to form interconnection dense and fine gel network structures under confocal laser scanning microscopy (CLSM) after heat treatment, untreated MPC gels at pH 3 and pH 9 showed dense network structures compared to other gels. Also, ultrasound treatment led to finer and more homogeneous gel network structures. Microstructure images and rheological measurements of emulsions revealed that emulsions stabilized by sonicated MPC at pH 3 had the smallest oil droplet size with D [3,2] ~6.5 µm and D [4,3] ~12.7 µm, respectively. The gel strength (G' (1 Hz)) of pH 3 emulsion was the highest and reached ~502.3 Pa. Emulsion stabilized by sonicated MPC at pH 5 had the lowest G' (1 Hz) at ~107.9 Pa, the oil droplet was the greatest among all emulsions with D [3,2] ~20.4 µm and D [4,3] ~66.9 µm, respectively. This could be attributed to MPC dispersion at pH 5 having the lowest solubility and the greatest particle size. For heat induced MPC gels, ultrasound treatment declined the gel strength at all pH values; gels without ultrasound treatment at pH 9 and pH 3 had the highest G'. The study may provide useful information for MPC applications in the food field. The second study examined the viscoelastic properties of heat-induced defatted mussel protein gels with varying concentrations (0%, 2.5%, 5%, 10% w/w) of native rice starch (NRS), waxy rice starch (WRS), waxy corn starch (WCS), and waxy potato starch (WPS). CLSM images showed that a 10 w/w % mussel protein concentrate (MPC) sample cannot form a gel after heating at 90 ℃ for 30 min. When 5% starch was added to MPC samples, dense gel network structures were observed after heating, suggesting a crucial role of starch in MPC gelation. Rheological measurements indicated that starch addition can increase the strength of MPC gels. Both G′ and Gʺ raised significantly in the protein-starch system when the starch concentration increased. Compared to the control (10% MPC without starch), in the presence of 10% starches, the G′ of MPC-NRS, MPC-WRS, MPC-WCS, MPC-WPS gels increased ~120, ~32, ~50, ~185 times, respectively. MPC-WPS gel appeared the highest G′ among all MPC-starch gels with a 10% starch addition. In the protein-starch system, the combination of MPC and starch resulted in a stronger gel, showing a greater effect than the sum of MPC and starch separately. Additionally, the pasting temperature of starch in the protein-starch system was higher compared to when it was in water.
Embargoed until 28th July 2026
Keywords: 400406 Powder and particle technology